First experiences with participatory climate services for farmers in Central America: A case study in Honduras - Giraldo, Diana; Clarkson, Graham; Dorward, Peter; Obando, Diego (AAD, 2024)
While climate services for small-scale farmers are gaining recognition for contributing to adaptation and resilience to climate variability and change, their provision in developing countries remains a critical challenge. Effective climate services consider why and how farmers of varied socioeconomic background make relevant decisions avoiding the traditional prescriptive forms of transfer that merely focus on delivering climate information. Evidence from sub-Saharan Africa shows that climate services for agriculture generates transformations in how farmers access and use climate information, as well as changes in farmer decision-making. In this paper, we address the question of whether the same effect is also seen in Latin America, where farming systems, farming decisions, socioeconomic contexts and non-climate constraints are very different to those of Africa. A group of 209 farmers in the dry corridor in Honduras was studied. We find that 98% of the trained farmers did uptake and use the climate information, and some 73% expressed that the agroclimatic information was key to the success of their harvest despite the challenging 2019 season. Some 43% of the farmers made changes in farming practices. In particular, farmers changed the crop they grew, the crop and land management, the planting dates, inputs and crop varieties. These changes reportedly had positive effects on their food security, and income. These findings support the hypothesis that Participatory Integrated Climate Services for Agriculture (PICSA) plays a positive role in providing effective climate services in Central America, improving decision-making, and enabling farmers to make their own decisions based on the analysis of information and their demands regardless of their level of literacy. We pose that participatory climate services in agriculture can catalyse processes of long-term transformation in farming systems, notably through lifting farmers out of poverty and food insecurity and providing an integrated approach to make informed decisions in the face of climatic variation.